Cancer virus hunters a history of tumor virology - Morgan, Gregory J. (Johns Hopkins University Press, 2022)
"The author tells a history of the study of cancer-causing viruses from the early twentieth century to the development of an HPV vaccine for cervical cancer in 2006. He profiles the "cancer virus hunters" who made breakthroughs in tumor virology"--